Exposure to agrochemicals and markers of kidney damage among farmers in rural communities in Southwestern Nigeria (2021)
Background: Chronic kidney disease of unknown origin (CKDu) is assuming an epidemic proportion, especially in farming communities worldwide. We explored the relationship between CKD markers and agrochemical exposure among rural farmers in South Western Nigeria. Methods: We studied selected farming communities in Southwestern Nigeria where the use of agrochemicals was widespread. A pre-tested questionnaire was administered to participants. Anthropometric data, information on use of agrochemicals; urine and blood samples were obtained. Informed consent was obtained from participants. The study was approved by the Institutional Ethics committee and complied with 1975 Helsinki declaration, as revised in 2000. Results: A total of 438 farmers made up of 202 males (46.1%) and 236 females (53.9%) were studied. The mean microalbuminuria was 30.2 ±11.7 mg/dl. Majority of the farmers had CKD stage 2 (42.0%) and CKD stage 3 (37.7%). The type of farming engaged in had a positive, but not significant, correlation with eGFR (r=0.012, p=0.832). There was positive correlation between type of farming and GFR category (r=0.24, p=0.000). Frequency of use of hexachlorocyclohexane had a positive and significant correlation with eGFR (r=0.111, p=0.045). Annual crop farming had a correlation with UACR (r=0.149, p=0.024). Conclusion: Annual crop farming had a positive correlation with UACR, eGFR and GFR category. The prolonged use of agrochemicals on an annual basis can cause kidney damage.